Perspektif Mahasiswa dalam Upaya Mempertahankan Wujud Bela Negara Serta Ketahanan Nasional - Intan Camelia; Dinda Wulandari; Ilda Safitri; Nadia Cahya Rahma Nasution; Nailah Putri Maharani Susanto; Salsabillah Luthfiyyahningtyas; Septi Fatma Khairani; Sri Yunita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of this research was to find out: (1) if colleger understand about defending the country in civic courses, (2) how the implementation is carried out to defend the country, (3). Knowing how to grow the attitude of defending the country. This research was conducted on September 24, 2022 until September 27, 2022, conducted on several colleger inside and outside the Universitas Negeri Medan through google form room. This study uses a qualitative descriptive method, namely research conducted to examine an object, condition, a group of people, or other phenomena with natural conditions in order to make a systematic overview or detailed description factual and accurate. Colleger already understand the attitude of defending the country, and it can be done through small things. Pancasila is a guideline in fostering an attitude of defending the country, through the precepts contained in the Pancasila which can be applied daily.